The effect of camera pan on the two-dimensional direct linear transformation and scalar reconstruction techniques when applied to ergometer rowing - Warmenhoven, J.; Ball, N.; Draper, C.; Hunter, A. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Changes in camera pan may affect reconstruction accuracy of two-dimensional (2D) kinematic data collected in on-water rowing testing. The 2D direct linear transformation (2D-DLT) may assist in improving reconstruction accuracy of rowing kinematics when a perpendicular camera changes position. Accuracy of the 2D-DLT and scalar reconstruction techniques was compared using coefficient of multiple correlations (CMCs), range of motion difference (ROMDiff) and root mean square error (RMSE). 2DDLT was found to have significantly greater accuracy (CMC and RMSE; p<0.05) for the ankle and knee. 2D-DLT also had significantly greater accuracy (p<0.05) for the knee and hip in ROMDiff. However, offset errors were found for the hip (CMCs and RMSE) and are potentially due to kinematic offsets derived from out-of-plane location of markers.